Cytokine overproduction and crosslinker hypersensitivity are unlinked in Fanconi anemia macrophages. Issue 3 (2nd October 2015) - Garbati, Michael R.; Hays, Laura E.; Rathbun, R. Keaney; Jillette, Nathaniel; Chin, Kathy; Al‐Dhalimy, Muhsen; Agarwal, Anupriya; Newell, Amy E. Hanlon; Olson, Susan B.; Bagby, Grover C.
Abstract : TLR‐activated FANCC‐deficient macrophages overproduce inflammatory cytokines and sustain DNA damage, where induced DNA damage is not required to sustain aberrant cytokine responses. Abstract : The Fanconi anemia proteins participate in a canonical pathway that repairs cross‐linking agent‐induced DNA damage. Cells with inactivated Fanconi anemia genes are universally hypersensitive to such agents. Fanconi anemia‐deficient hematopoietic stem cells are also hypersensitive to inflammatory cytokines, and, as importantly, Fanconi anemia macrophages overproduce such cytokines in response to TLR4 and TLR7/8 agonists. We questioned whether TLR‐induced DNA damage is the primary cause of aberrantly regulated cytokine production in Fanconi anemia macrophages by quantifying TLR agonist‐induced TNF‐α production, DNA strand breaks, crosslinker‐induced chromosomal breakage, and Fanconi anemia core complex function in Fanconi anemia complementation group C‐deficient human and murine macrophages. Although both M1 and M2 polarized Fanconi anemia cells were predictably hypersensitive to mitomycin C, only M1 macrophages overproduced TNF‐α in response to TLR‐activating signals. DNA damaging agents alone did not induce TNF‐α production in the absence of TLR agonists in wild‐type or Fanconi anemia macrophages, and mitomycin C did not enhance TLR responses in either normal or Fanconi anemia cells. TLR4 and TLR7/8 activation induced cytokine overproduction in Fanconi anemia macrophages. Also, although TLR4 activation was associated with induced double strand breaks, TLR7/8 activation was not. That DNA strand breaks and chromosome breaks are neither necessary nor sufficient to account for the overproduction of inflammatory cytokines by Fanconi anemia cells suggests that noncanonical anti‐inflammatory functions of Fanconi anemia complementation group C contribute to the aberrant macrophage phenotype and suggests that suppression of macrophage/TLR hyperreactivity might prevent cytokine‐induced stem cell attrition in Fanconi anemia.